Land Administration In Supporting Digital Era: An Experience and Effect To The Land Acquisition - Ahmad Hamidi Mohamed; Noorfajri Ismail; Kamilah Wati Mohd (RSIS International, 2025)
International Journal of Research and Innovation in Social Science Volume : IX No: 2 (page: 4172–4180)